Shenkang Injection and Its Three Anthraquinones Ameliorates Renal Fibrosis by Simultaneous Targeting IƙB/NF-ƙB and Keap1/Nrf2 Signaling Pathways - Luo, Liang-Pu; Suo, Ping; Ren, Li-Li; Liu, Hong-Jiao; Zhang, Yamei; Zhao, Ying-Yong (Frontiers in Pharmacology, 2021)
Oxidative stress and inflammation are important and critical mediators in the development and progression of chronic kidney disease (CKD) and its complications. Shenkang Injection (SKI) was widely used to treat patients with CKD. Although the anti-oxidative and anti-inflammatory activity was involved in SKI against CKD, its bioactive components and underlying mechanism remains enigmatic. Rat model of adenine-induced chronic renal failure (CRF) is associated with, and largely driven by, oxidative stress and inflammation. Hence, we identified the anti-oxidative and anti-inflammatory components of SKI and further revealed their underlying mechanism in the adenine-induced CRF rats. Compared with control rats, the levels of creatinine, urea, uric acid, total cholesterol, triglyceride and low-density lipoprotein cholesterol in serum were significantly increased in the adenine-induced CRF rats. However, treatment with SKI and three anthraquinones including chrysophanol, emodin and rhein could reverse these aberrant changes. They could significantly inhibited pro-fibrotic protein expressions including collagen I, α-SMA, fibronectin and vimentin in the kidney tissues of the adenine-induced CRF rats. Of note, SKI and rhein showed the stronger inhibitory effect on these pro-fibrotic protein expressions than chrysophanol and emodin. Further, they could improve dysregulation of IƙB/NF-ƙB and Keap1/Nrf2 signaling pathways. Chrysophanol and emodin showed the stronger inhibitory effect on NF-κB p65 protein expression than SKI and rhein. Rhein showed the strongest inhibitory effect on p65 downstream target gene products including NAD(P)H oxidase subunits (p47phox, p67phox and gp91phox) and COX-2, MCP-1, iNOS and 12-LO in the kidney tissues. However, SKI and rhein showed the stronger inhibitory effect on the significantly downregulated anti-inflammatory and anti-oxidative protein expression nuclear Nrf2 and its target gene products including HO-1, catalase, GCLC and NQO1 in Keap1/Nrf2 signaling pathway than chrysophanol and emodin. This study first demonstrated that SKI and its major components protected against renal fibrosis by inhibiting oxidative stress and inflammation via simultaneous targeting IƙB/NF-ƙB and Keap1/Nrf2 signaling pathways, which illuminated potential molecular mechanism of anti-oxidative and anti-inflammatory effects of SKI.